The Healthy Eating, Active Living (HEAL) Study: Outcomes, Lessons Learnt and Future Recommendations. (24th January 2017) - Cox, Rachael; Skouteris, Helen; Fuller‐Tyszkiewicz, Matthew; Watson, Brittany; Jones, Amanda D.; Omerogullari, Stella; Stanton, Kelly; Bromfield, Leah; Hardy, Louise L.
Abstract : Internationally, there are few interventions that promote healthy lifestyles in the out‐of‐home care (OOHC) sector. The aim of this quantitative study was to measure the efficacy of the Healthy Eating, Active Living (HEAL) programme for young people who live in residential OOHC and their carers. Seventy young people and 177 carers were recruited between August 2012 and October 2014 from 48 residential care units across metropolitan Melbourne and regional Victoria, Australia. The HEAL programme included educational sessions for young people, and professional development for carers to foster healthy eating and physical activity. Young people and carers completed questionnaires measuring behavioural, psychosocial and motivational outcomes. Objective measures of height and weight were collected for young people and self‐reported by carers. The findings revealed no evidence for the efficacy of the HEAL intervention for either young people or carers. The most likely explanation for the null result was difficulties associated with: (1) collecting quantitative data for evaluative purposes in vulnerable populations (particularly the impact of attrition on statistical power); and (2) implementing interventions in complex environments. We conclude with a summary of lessons learnt and recommendations for future research in this unique setting. Copyright © 2017 John Wiley & Sons, Ltd. 'Quantitative study… to measure the efficacy of the HEAL programme for young people who live in residential OOHC and their carers' Key Practitioner Messages: There are a number of challenges inherent to collecting longitudinal data and/or employing a randomised trial design in this setting. Researchers working in this area need to acknowledge the critical need for this type of research but also consider alternative approaches to data collection. It is integral that organisational practices and/or policies are in place so that a HEAL philosophy is embedded in the residential OOHC culture; in other words, HEAL becomes a part of each organisation's values, goals and shared expectations.